Polygyny and intimate partner violence in sub-Saharan Africa: Evidence from 16 cross-sectional demographic and health surveys - Bright Opoku Ahinkorah (Elsevier, 2021)
In sub-Saharan Africa, where intimate partner violence has been found to be predominant, several scholars have made efforts to understand its predictors. Socio-culturally, polygyny has been considered as a key determinant of intimate partner violence. This study aimed to examine the association between polygyny and intimate partner violence in 16 sub-Saharan African countries. Binary logistic regression models were used in testing the association and the results were presented as crude and adjusted odds ratios at 95% confidence interval. The proportion of women in polygamous marriages in the 16 countries was 20.2%, ranging from as high as 40% in Chad to as low as 1.6% in South Africa. The prevalence of IPV was 30.7% in the 16 countries, ranging from as high as 44% in Uganda to as low as 12.7% in South Africa. The odds of IPV were higher among women in polygamous marriages in Angola, Burundi, Ethiopia, Uganda, Malawi, Mozambique, Zambia and Zimbabwe but was lower among women in polygamous marriages in Cameroon [COR = 0.54, 95% CI = 0.44-0.66] and Nigeria [COR = 0.61, 95% CI = 0.55-0.67], and this persisted after controlling for level of education, place of residence, wealth quintile, media exposure, and justification of violence. This study has found a significant association between polygyny and intimate partner violence. The practice of intimate partner violence in sub-Saharan Africa is fused into the socio-cultural norms and religious traditions of most countries in the sub-Saharan African region. The findings imply that family structures expose women to intimate partner violence. Therefore, global efforts in dealing with intimate partner violence through the Sustainable Development Goals should be done with attention on the socio-cultural norms and traditions around marriage and family structures.